ANALYSIS ON THE STUDENTS PROBLEMS IN COMPREHENDING NARRATIVE TEXTS - F42106096, Sarwo; Susilawati, Endang; Riyanti, Dwi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2013)
Abstrak: PenelitianiniadalahtentanganalisiskemampuansiswapadapemahamanteksbacaannarasiolehSiswaKelas VIII SMP KemalaBhayangkariKubu Raya di TahunAkademik 2012/2013. Tujuandaripenelitianiniadalahuntukmengetahuiseberapabaikkemampuanmahasiswadalammemahamiteksnarasi.penelitianinidiharapkanakanbermanfaatbagi guru dansiswadalambahasa proses belajarmengajar. Metode yang digunakandalampenelitianiniadalahpenelitiandeskriptif yang bertujuanuntukmenggambarkankarakteristikmatapelajaran.PopulasidaripenelitianiniadalahsiswaKelasdelapan SMP KemalaBhayangkariKubu Raya di TahunAkademik 2012/2013.Jumlahsampelpenelitianiniadalah 30 siswa.Teknik yang digunakanuntukmengumpulkan data adalahteknikpengukurandanteknikobservasilangsung.Alatpengumpulan data adalahtespemahamanbacaan.Berdasarkantemuanpenelitian, parasiswamasihlemahdalammemahamibacaan.Merekalemahdalammenemukanorientasi, komplikasi, resolusi, reorientasidankosa kata. Kata Kunci: teksnarasi, analisis, membaca. Abstract: The research is about analysis on theability of the students on comprehending narrative text reading ofthe Eighth Grade Students of SMP KemalaBhayangkariKubu Raya in Academic Years 2012/2013. The objective of the study is to know how well the Students ability in comprehending narrative text. It is expected that the research would be useful for the teachers and students in language teaching and learning process. The method used in this research is a Descriptive Research whichis aimed at describing the characteristics of subjects. The population of the study was the eight Grade Students of SMP KemalaBhayangkariKubu Raya in Academic Years 2012/2013. The number of research samplewas 30 students. The technique used for collecting data was measurement technique and direct observation technique. The tool of collecting data was reading test. Based on the research finding, the students were still weak at reading comprehension. They were weak at finding orientation, complication, resolution, reorientation and vocabulary. Keywords: Narrative text, analysis, reading.